Preclinical Pharmacology in the Rhesus Monkey of CW 1759-50, a New Ultra-short Acting Nondepolarizing Neuromuscular Blocking Agent, Degraded and Antagonized by L-Cysteine. (November 2018) - Savarese, John J.; Sunaga, Hiroshi; McGilvra, Jeff D.; Belmont, Matthew R.; Murrell, Matthew T.; Jeannotte, Erin; Cooke, Farrell E.; Wastila, William B.; Heerdt, Paul M.
Editor's Perspective: What We Already Know about This Topic: Gantacurium is an ultra-short acting nondepolarizing neuromuscular blocking agent in the monkey and in man that is degraded nonenzymatically by adduction of L-cysteine under physiologic conditions Administration of gantacurium results in decreased mean arterial pressure and increased heart rate What This Article Tells Us That Is New: CW 1759-50 is a new nondepolarizing neuromuscular blocking agent that may have a clinical profile that is superior to that of gantacurium Studies in rhesus monkeys comparing CW 1759-50 with gantacurium found both of them to be ultra-short acting because of their rapid degradation by L-cysteine adduction The effects of CW 1759-50 on mean arterial pressure and heart rate were substantially less than those of gantacurium Background: Structure–activity studies were performed to identify a new neuromuscular blocking agent retaining the ultra-short acting characteristics of gantacurium, including degradation and reversal by L-cysteine, but lacking its histaminoid properties in man. CW 1759-50 has emerged from this program. Methods: Adduction of CW 1759-50 with L-cysteine was studied by high-performance liquid chromatography and mass spectrometry. Institutional Animal Care and Use Committee–approved comparisons of CW 1759-50 to gantacurium were performed in rhesus monkeys. ED95 for neuromuscular blockade was established. Spontaneous recovery was compared to reversal by L-cysteine in paired studies of boluses or infusions. In addition, changes in mean arterial pressure and heart rate after very large doses of 15 to 60 × ED95 were compared. Results: The half-time of adduction of L-cysteine to CW 1759-50 in vitro was 2.3 min. The ED95 of CW 1759-50 was 0.069 ± 0.02 mg/kg; ED95 of gantacurium was 0.081 ± 0.05 mg/kg ( P = 0.006). Duration of action (recovery to 95% twitch height after 98 to 99% blockade) was as follows: CW 1759-50, 8.2 ± 1.5 min; and gantacurium, 7.4 ± 1.9 min; (n = 8 and 9, P = 0.355). Administration of L-cysteine (30 mg/kg) shortened recovery ( i.e., induced reversal) from CW 1759-50 after boluses or infusions ( P always less than 0.0001). Recovery intervals (5 to 95% twitch) ranged from 6.1 to 6.7 min (and did not differ significantly) after boluses of 0.10 to 0.50 mg/kg, as well as control infusions ( P = 0.426 by analysis of variance). Dose ratios comparing changes of 30% in mean arterial pressure or heart rate to ED95 for neuromuscular blockade (ED 30% Δ [mean arterial pressure or heart rate]/ED95) were higher for CW 1759-50 than for gantacurium. Conclusions: CW 1759-50, similar to gantacurium, is an ultra-short acting neuromuscular blocking agent, antagonized by L-cysteine, in the monkey. The circulatory effects, however, are much reduced in comparison with gantacurium, suggesting a trial in humans. Abstract : CW 1759-50 is a new nondepolarizing neuromuscular blocking agent that may have a clinical profile that is superior to that of gantacurium. Studies in rhesus monkeys comparing CW 1759-50 with gantacurium found both of them to be ultra-short acting because of their rapid degradation by L-cysteine adduction. The effects of CW 1759-50 on mean arterial pressure and heart rate were substantially less than those of gantacurium.